Overtopping risk of high-hazard embankment dam under climate change condition - Wan Noorul Hafilah Wan Ariffin; Lariyah Mohd Sidek; Hidayah Basri; Noorhayati Idros; M. Torres Adrian; Noor Hisham Abd Ghani; Hazri Mohd Khambali; Siti Mariam Allias Omar; Muhammad Izzat Azhar Khebir; Ali Najah Ahmed (PLoS ONE, 2025)
Climate change poses an escalating threat to the safety of high-hazard embankment dams, increases flood discharge impacting dam overtopping risk by altering the hydrological load of the original dam designed capacity. This paper’s primary aims are to evaluate climate change’s influence on extreme rainfall events and their impact on dam safety and to assess the overtopping risk of Batu Dam under various climate scenarios. This study focusses on assessing the overtopping risk of Batu Dam in Malaysia, utilizing regional climate model projections from the Coupled Model Intercomparison Project 5 (CMIP5) spanning 2020 to 2100. Three Representative Concentration Pathways (RCPs)—RCP4.5, RCP6.0, and RCP8.5 as the scenario and divide into 3 period of study: early century (2020–2046), mid (2047–2073) and late-century (2074–2100) evaluated with hydrological analysis to access the dam safety. Using the Linear Scaling Method (LSM), we corrected the bias projection rainfall data from three Regional Climate Models (RCMs) for the RCPs. Future Probable Maximum Precipitation (PMP) was estimated using statistical analysis techniques developed by the National Hydraulic Research Institute of Malaysia (NAHRIM). Additionally, Rainfall Intensity-Duration-Frequency (IDF) curves were updated based on climate scenarios outlined in the Hydrological Procedure 2021 and the associated Climate Change Factors. The HEC-HMS hydrological model was employed to simulate PMF and IDF for ARIs ranging from 1 to 100,000 years, providing a comprehensive analysis of risks under future climatic conditions. Across all future climate scenarios, inflow events were projected to exceed the dam design inflow, with RCP8.5 indicating the highest inflow values, particularly later in the century, highlighting probability of overtopping risks. Late-century projections show inflow for ARI 50 under RCP8.5 exceeding PMF by 20%, while mid-century RCP6.0 results indicate a 15% higher inflow for ARI 50000. Early-century RCP4.5 shows a 10% increase for ARI 100000 compared to PMF. The study advocates adaptive dam safety management and flood protection measures. This research provides crucial insights for embankment dam owners, stressing the urgent need to address Batu Dam’s vulnerability to extreme flooding amidst climate change and emphasizing proactive measures to fortify critical infrastructure and protect downstream communities.